Antibiotic resistance and usage, a survey on the knowledge, attitude and practices among the medical students of a southern Indian teaching hospitals - Regidi, Swathi Ratnam; Mallika, Billa S. B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Examining the knowledge, attitude and practices (KAP) of the medical students regarding antibiotic resistance (ABR) and use can help us in devising suitable educational interventions for them, tailored according to their earlier held knowledge, beliefs, capabilities and experience. Methods: A cross sectional, questionnaire based survey was conducted among medical students of a teaching hospital, whereby their KAP regarding antibiotic use and resistance was assessed by using a questionnaire, whose responses ranged from ‘agree’ to ‘disagree,’ ‘always to never’ and true / false. The data was analysed by using simple descriptive statistics. Wherever it was relevant, the Chi-square test was used to determine any significant difference. Results: The number of medical students who agreed that ABR was an important and a serious public health issue in this teaching hospital was 76 percent (n = 325). But, only 54.3% (n = 233) of the students were aware that bacteria were not responsible for causing cold and flu, while the remaining 37.2 percent (n = 22) were not knowledgeable about this fact. More than 80% rated the adverse effect profile of the antibiotic and the risk of a super infection as the important factors which deserved consideration. Cost of the antibiotic was considered to be an important factor deserving consideration by only 65.5% (n=277) of the participants. Conclusions: Our survey revealed that most of the students were aware of the antimicrobial resistance and its consequences. The only concern was their casual attitude regarding the antibiotic use. Further educational interventions are necessary to improve their understanding and perceptions on antibiotic resistance, as well as their attitude towards antibiotic use.